FORMULASI PATCH KOSMETIK LENDIR BEKICOT (Achatina fulica) DENGAN POLIMER KITOSAN DAN BERBAGAI VARIASI AMILUM - Michrun Nisa; Andi Nuraisyah; Nurul Arfiyanti Yusuf; Nurul Alifah K (Jurnal Ilmiah Manuntung, 2016)
The research on cosmetic patch formulation containing snail slime with a variety starch was aimed to determine the type of starch that could produce a patch preparation with a good physical characteristic had been conducted. Cosmetic patch formulation of snail slime was using combination of chitosan and starch polymers such as corn, potato and tapioca starch. The method was used the solvent evaporation technique. The evaluation of patches include weight uniformity, folding endurance, thickness, moisture content, moisture uptake and stability of the patch. The combination of chitosan and starch polymers produced patches that had pH 5 with color uniformity, smoothness of surface and easily removed from the mold. The results showed that patches containing tapioca starch gave weight uniformity that did not much different on each replication that was 0,568 ± 0,03. Patches containing corn starch provided thickness values on each replication did not much different from 0,16± 0,01. Patches containing potato and tapioca starch produced patches that was accordance with the standard parameter of folding endurance was more than 200 times. Patches containing corn and tapioca starch producing patches accordance with the standard parameter of moisture content were less than 10 %. Patches containing potato starch gave patch a high moisture uptake that was 8,2%. The combination of chitosan and tapioca strach as polymers produced patch preparation with a good characteristic on the formulation of snail slime cosmetic patch.